FAKTOR RISIKO KEJADIAN DM PADA USIA DEWASA - Nurman, Zurni; Yuska, Defniwita; Laila, Wilda; Adfar, Tika Dwita (Ensiklopedia of Journal, 2025)
Abstract: Puskesmas Glugur Darat is one of the Puskesmas in Medan City that has a high prevalence of diabetes. The general objective of this study was to determine the risk factors for the incidence of DM in adulthood. The research design used in this study was case control. The study was conducted at the Glugur Darat Health Center Work Area in August 2024. The population is people who seek treatment and live in the Glugur Darat Health Center working area with a total of 36,245 people. The sample has a ratio of 1: 1 which includes a case sample of 88 respondents and a control sample of 88 respondents. The sampling technique used in this study was Simple Random Sampling. Data analysis was done univariate and bivariate. The results showed there was a relationship between family history (p value: 0.003) and age (p value: 0.028). It is recommended that people strive to maintain blood sugar levels by preventing and finding out information related to risk factors that can cause diabetes mellitus through social media and health facilities that distribute brochures or from other health banners.Keywords: Diabetes, Family History, Age